2012
DOI: 10.1371/journal.pone.0037513
|View full text |Cite
|
Sign up to set email alerts
|

Global Activation of CD8+ Cytotoxic T Lymphocytes Correlates with an Impairment in Regulatory T Cells in Patients with Generalized Vitiligo

Abstract: Melanocyte-specific CD8+ cytotoxic T lymphocytes (CTLs) play a pivotal role in vitiligo-induced depigmentation. Yet, the mechanisms underlying the high frequency of generalized autoimmune disorders associated with generalized vitiligo (GV) are unknown. We hypothesized that an imbalance between activated CD8+ CTLs and regulatory T cells (Tregs) exists in patients with GV . Assessment of the circulating CD8+ CTLs and Tregs by flow cytometric analysis revealed an obvious expansion of CD8+ CTLs and a concomitant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
124
1
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 147 publications
(158 citation statements)
references
References 30 publications
12
124
1
13
Order By: Relevance
“…Such alterations might lead to the higher levels and activation of cytotoxic T cells (Fig. 1) which have been reported in individuals with the disease [10,11]. Currently, however, studies examining any reciprocal relationship between CD4 + CD25 + FoxP3 + Tregs and CD8 + in vitiligo progression are lacking.…”
Section: Regulatory T Cells In Vitiligomentioning
confidence: 97%
See 4 more Smart Citations
“…Such alterations might lead to the higher levels and activation of cytotoxic T cells (Fig. 1) which have been reported in individuals with the disease [10,11]. Currently, however, studies examining any reciprocal relationship between CD4 + CD25 + FoxP3 + Tregs and CD8 + in vitiligo progression are lacking.…”
Section: Regulatory T Cells In Vitiligomentioning
confidence: 97%
“…More recently, repigmentation in a mouse model of spontaneous epidermal depigmentation was found to be accompanied by an increased Treg cell infiltration, suggesting their importance in preventing an ongoing immune response against melanocytes [17]. To date, several studies have indicated perturbations in Treg cell numbers and/or function in vitiligo patients [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Such alterations might lead to the higher levels and activation of cytotoxic T cells (Fig.…”
Section: Regulatory T Cells In Vitiligomentioning
confidence: 99%
See 3 more Smart Citations